2017
DOI: 10.9778/cmajo.20170089
|View full text |Cite
|
Sign up to set email alerts
|

The relation between promotional spending on drugs and their therapeutic gain: a cohort analysis

Abstract: journal advertisements by the Canadian Pharmaceutical Advertising Advisory Board, there is no a priori reason to believe that the situation in Canada is either the same as or different from the one south of the border. This study looks at the most heavily promoted drugs and the therapeutic gain from those products. It also compares the therapeutic gain from the most-promoted drugs and the topselling drugs by dollar value. Examining whether the medicines that are heavily promoted are the ones that provide the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 3 publications
0
21
0
5
Order By: Relevance
“…However, detailing is often a mixture of scientific evidence and promotional marketing that physicians have difficulty separating . In addition, several studies examining the therapeutic value of the most aggressively promoted drugs have indicated that these drugs are less innovative, possess little/no value over existing medications, and have generic substitutes . Furthermore, a number of studies have found evidence that transfers are associated with higher prescription costs and lower quality prescriptions implying that transfers may create an undue COI …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, detailing is often a mixture of scientific evidence and promotional marketing that physicians have difficulty separating . In addition, several studies examining the therapeutic value of the most aggressively promoted drugs have indicated that these drugs are less innovative, possess little/no value over existing medications, and have generic substitutes . Furthermore, a number of studies have found evidence that transfers are associated with higher prescription costs and lower quality prescriptions implying that transfers may create an undue COI …”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies examining the therapeutic value of the most aggressively promoted drugs have indicated that these drugs are less innovative, possess little/no value over existing medications, and have generic substitutes. 7,8 Furthermore, a number of studies have found evidence that transfers are associated with higher prescription costs and lower quality prescriptions implying that transfers may create an undue COI. [9][10][11][12] Given the potential dangers associated with transfers and COI, developed guidelines for managing COIs.…”
mentioning
confidence: 99%
“…This orientation is reflected in a statement about the role of pharmaceutical sales representatives issued by Rx&D, the predecessor to IMC: “Provider-supported detailing generates awareness about new treatments and provides science-based and Health Canada approved advice on how to administer these medications” [ 14 ]. Previous research that examined the most heavily promoted products in Canada, showed that the vast majority of spending went to medications that offered little to no additional therapeutic value over existing therapies [ 15 ]. The comprehensiveness of the safety information provided by sales representatives when they visit doctors was investigated in a study involving primary care practitioners in Vancouver and Montreal.…”
Section: Discussionmentioning
confidence: 99%
“…Not by chance, the published cost estimates for developing a new drug vary almost ten times from the lowest to the highest [19]. Then, aggressive marketing is still required to sell expensive medicines that often differ only marginally [18,20], with trendy 'personalized medicine' helping to create an ideal setting for price discrimination for new similar drugs [21]. Anticancer drugs can be considered an emblematic example of unsustainable prices [22].…”
Section: Discussionmentioning
confidence: 99%